Are fifth-grade students in elementary school during the COVID-19 pandemic in need of a jumping task-based worksheet to aid in the development of their knowledge? A needs analysis explained - Rahmat Hidayat; Pramudiyanti Pramudiyanti; Handoko Handoko (Lighthouse Publishing, 2022)
The COVID-19 pandemic has forced the education process to be conducted online to avoid face-to-face education patterns. During the pandemic, however, many schools are still failing and experiencing the ineffectiveness of online learning systems. The urgency is that if this condition is not addressed and continues, students may experience a loss of learning, resulting in a lack of enthusiasm to learn at school and, as a result, a decline in cognitive testing results. During the pandemic, learning at the SD Karya Penggawa area, Pesisir Barat Lampung, was less effective, resulting in low student cognitive assessment outcomes. The goal of this study was to assess the need for LKPD development using HOTS-based LKPD Jumping Tasks (High Order Thinking Skills). The method used was a qualitative descriptive research method by conducting a needs analysis. Research data were obtained from interviews and questionnaires. Needs analysis questionnaires were given to teachers and grade 5 students in the Elementary Schools of the Karya Penggawa area. The results of the study revealed that the development of HOTS-based LKPDs needed to be carried out in SD Karya Penggawa areas because students wanted more attractive LKPDs to prevent loss of learning during the Covid-19 pandemic. Besides, it was also revealed that teachers wanted training on the implementation of LKPD jumping tasks to improve the quality of learning.